Calcareous sponges (Porifera, Calcarea) from Ilha Grande Bay, Brazil, with descriptions of three new species - Azevedo, Fernanda; Klautau, Michelle (Zootaxa, 2007)
This is the first surveillance of calcareous sponges (Porifera, Calcarea) from Ilha Grande Bay in the Southwest coast of Rio de Janeiro, Brazil. Two islands were surveyed and the description of the calcareous sponges collected is presented here. A total of 98 specimens were collected, from five species. Clathrina aspina has its geographic distribution extended to the South of Rio de Janeiro state; Sycettusa cf. hastifera, a species from the Red Sea, and previously cited to the North of Rio de Janeiro state, was now found in Ilha Grande Bay; three new species to science are being described here: Clathrina angraensis sp. nov., Leucandra serrata sp. nov., and Paraleucilla perlucida sp. nov.